Job Crafting Training Design as an Effort to Increase Work Engagement on Workers - Irawati, Titiana; Sinambela, Frikson Christian (Psikostudia : Jurnal Psikologi, 2023)
Being a new member of an organization / company is expected by job seekers. Many prospective workers have participated in many selections but have not succeeded in becoming members of the organization as expected. So a strategy (intervention) is needed from management in order to increase worker work engagement. The right design according to the results of the study is the design of job crafting training which theoretically is one of the predictors of work engagement. The purpose of this study is to develop a training design to increase work engagement in PT X workers through job crafting. The research method in this study is quantitative. The researcher provided 9 (nine) open-ended questions related to self-development and challenges faced at PT X. The questions were uploaded on the Google Form, making it easier for participants to fill in anytime and anywhere. After respondents filled out the questionnaire, researchers coded each answer response. The results of the study can be concluded that the design of job crafting training is one design that deserves to be considered by organizations in order to develop human resources, especially for new workers. The implementation of training by the organization is expected to provide experience for new workers so as to increase worker work engagement. It is expected that with the increase in work engagement, performance will also increase. The implications of this study require the legality aspect of human resource development, especially new employees, should be outlined in the rules/policies/SOPs so that the guarantee of implementing activities is higher.Menjadi anggota baru pada suatu organisasi/perusahaan merupakan hal yang diharapkan oleh pencari kerja. Banyak calon pekerja yang mengikuti banyak seleksi namun belum berhasil menjadi anggota organisasi sesuai harapannya. Maka dibutuhkan strategi (intervensi) dari manajemen dalam rangka meningkatkan work engagement pekerja. Adapun desain yang tepat sesuai dengan hasil kajian adalah desain pelatihan job crafting yang secara teoritis merupakan salah satu prediktor dari work engagement. Tujuan dari penelitian ini adalah menyusun desain pelatihan untuk meningkatkan work engagement pada pekerja PT X melalui job crafting. Metode penelitian pada penelitian ini adalah kuantitatif. Peneliti memberikan 9 (sembilan) pertanyaan terbuka terkait pengembangan diri dan tantangan yang dihadapi di PT X. Pertanyaan tersebut  diunggah pada Google Form sehingga memudahkan peserta untuk melakukan pengisian kapan pun dan dimana pun. Setelah responden mengisi kuesioner, peneliti melakukan Coding setiap respons jawaban yang muncul. Hasil penelitian dapat disimpulkan bahwa desain pelatihan job crafting merupakan salah satu desain yang layak dipertimbangkan oleh organisasi dalam rangka mengembangkan sumber daya manusia terutama bagi pekerja baru. Implementasi pelatihan oleh organisasi diharapkan dapat memberikan pengalaman bagi pekerja baru sehingga mampu meningkatkan work engagement pekerja. Diharapkan dengan meningkatnya work engagement maka kinerja juga akan mengalami peningkatan. Implikasi dari penelitian ini perlu adanya aspek legalitas pengembangan sumber daya manusia terutama karyawan baru sebaiknya dituangkan pada aturan/kebijakan/SOP sehingga jaminan pelaksanaan kegiatan lebih tinggi.